Control of Investment versus Control of Return - Meriam, R. S. (Quarterly Journal of Economics, 1930)
Journal Article Control of Investment versus Control of Return: A Criticism Get access R. S. Meriam R. S. Meriam Graduate School of Business Administration, Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 3, May 1930, Pages 549–552, https://doi.org/10.2307/1885797 Published: 01 May 1930